Synthesis and Analysis of Copper Neem (Azadirechta Indica) Soap-Nitro and Ethoxy Benzothiazole Complexes for Anti-Bacterial Activity Related with Skin Diseases - Kumawat, Priyanka; Sharma, Rashmi; Sharma, Nitin (Journal of Advanced Pharmaceutical Science And Technology, 2018)
The solid copper(II) soap derived from Neem (Azadirechta Indica)oil and its complex with ligand containing nitrogen, sulphur and oxygen atoms like 2-amino -6-nitro benzothiazole and 2-amino- 6-ethoxy benzothiazole have been synthesized and characterised by elemental analysis, IR spectroscopy and biological studies. From the analytical data, the stoichiometry of the complex has been observed to be 1:1 (metal:ligand). The derived compounds were found active against Staphylococcus aureus,Coagulase-negative staphylococci (CoNs), Acinetobacter baumanii, Pseudomonas aeruginosa and micrococcus bacteria. These findings have high medical, industrial and economic significance as copper (II) soap and copper (II) soap complex could be harnessed in the formulation of medicated soaps.
Keywords: Copper (II) Soap; Complexes; Elemental Analysis; IR Spectroscopic; Biological Studies